MptpA Kinetics Enhanced by Allosteric Control of an Active Conformation. Issue 17 (15th September 2022) - Maschietto, Federica; Zavala, Erik; Allen, Brandon; Loria, J. Patrick; Batista, Victor
Graphical abstract: Highlights: Allostery is an protein tyrosine phosphatases is an important biophysical problem. MD and solution NMR studies identified an allosteric site in Mycobacterium tuberculosis protein tyrosine phosphatase A. This allosteric site modulates catalytic activity through distal optimization of the active site. Electrostatic based eigenvector centrality measurements correlate well with NMR chemical shift perturbations to illuminate allosteric pathways. Abstract: Understanding allostery in the Mycobacterium tuberculosis low molecular weight protein tyrosine phosphatase (MptpA) is a subject of great interest since MptpA is one of two protein tyrosine phosphatases (PTPs) from the pathogenic organism Mycobacterium tuberculosis expressed during host cell infection. Here, we combine computational modeling with solution NMR spectroscopy and we find that Q75 is an allosteric site. Removal of the polar side chain of Q75 by mutation to leucine results in a cascade of events that reposition the acid loop over the active site and relocates the catalytic aspartic acid (D126) at an optimal position for proton donation to the leaving aryl group of the substrate and for subsequent hydrolysis of the thiophosphoryl intermediate. The computational analysis is consistent with kinetic data, and NMR spectroscopy, showing that the Q75L mutant exhibits enhanced reaction kinetics with similar substrate binding affinity. We anticipate that our findings will motivate further studies on the possibility that MptpA remains passivated during the chronic state of infection and increases its activity as part of the pathogenic life cycle of M. tuberculosis possibly via allosteric means.